Cidade sazonal: planejamento urbano para cidades litorâneas e o estudo de caso de Capão da Canoa - Carvalho, Guilherme de Oliveira (Universidade do Vale do Rio dos Sinos, 2021)
The Brazilian territorial occupation is developed for the most part close to the coast. This model of occupation over time created a series of cities that, not being the capitals or large metropolises, are considered regional development poles, exerting an influencing role over the others around them. Such cities receive seasonal flows of movement in certain periods, usually linked to high temperatures and vacation periods. These flows take place through tourism and second homes, present in the collective imagination of many people who wish to have a second home in order to enjoy their days close to the sea. This seasonal movement, when accentuated, can sometimes cause significant impacts on the city's infrastructure, which ends up having problems at times of greater movement, while remaining idle for most of the year. The occupation of coastal cities, however, is directly affected by this type of use, since it has a fixed population, normally linked to the provision of services and the development of this tourist trade. In this sense, it is noted that the urban development of these cities is focused on a framework for beautifying the spaces created for tourism and second residence. Thus, taking into account this situation, the fixed population often seems to remain far away from these spaces, occupying the areas furthest from the sea and not having the same urban quality as the floating population. Understanding these limits, analyzed from variables that impact the population's quality of life, is essential for urban planning in these cities. In this sense, the objective of this research is to create a tool to support the urban diagnosis of coastal cities, in order to contribute to their debate and planning. The methodology used was a case study with the municipality of Capão da Canoa, located on the north coast of Rio Grande do Sul, which has the characteristics described above. Through the production and analysis of maps, a methodology was created for superimposing relevant variables for the functioning of the city, seeking to understand the settlement places of fixed and floating populations, identifying the limits between them and the places of greatest need for investment, which they could articulate public power and private initiative. Finally, the results identify this system of spatial limits and the need for better structural planning in the medium and long term.
Keywords: Cidades litorâneas; Planejamento urbano; Turismo; Sazonalidade; Coastal cities; Urban planning; Tourism; Seasonality; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo